Investigation of the antibacterial activity of Ag-NPs conjugated with a specific antibody against Staphylococcus aureus after photoactivation - Kasing, Apun; Micky, Vincent; Devagi, Kanakaraju; Lesley, Maurice Bilung; Sia, Magdline Henry Sum; Al-Sharqi, Anes (Society for Applied Microbiology, 2019)
Aim: This work reports a new method for the use of lasers for the selective killing of bacteria targeted using light-absorbing Silver nanoparticles (Ag-NPs) conjugated with a specific antibody against the Gram-positive bacterium Staphylococcus aureus (S. aureus). Methods and Results: Ag-NPs were synthesized using a chemical reduction method and characterized with respect to their surface plasmon resonance, surface morphology via transmission electron microscopy (TEM) and dynamic light scattering (DLS). The bacterial surface was targeted using 20 nm Ag-NPs conjugated with an anti-protein A antibody. Labelled bacteria were irradiated with blue visible laser at 204 W/cm2. The antibacterial activity of functionalized Ag-NPs was investigated by fluorescence microscopy after irradiation, and morphological changes in S. aureus after laser treatment were assessed using scanning electron microscopy (SEM). The laser-irradiated, functionalized Ag-NPs exhibited significant bactericidal activity, and laserinduced bacterial damage was observed after 10 min of laser irradiation against S. aureus. The fluorescence microscopic analysis results supported that bacterial cell death occurred in the presence of the functionalized Ag-NPs. Conclusions: The results of this study suggest that a novel method for the preparation of functionalized nanoparticles has potential as a potent antibacterial agent for the selective killing of resistant disease-causing bacteria. Significance and Impact of the Study: This study shows that Ag-NPs functionalized with a specific antibody, could be used in combination with laser radiation as a novel treatment to target resistant bacterial and fungal pathogens with minimal impact on normal microflora.